1986
DOI: 10.1037/0022-3514.51.4.763
|View full text |Cite
|
Sign up to set email alerts
|

Effects of personal involvement: Thought-provoking implications for social loafing.

Abstract: In 1979, Latane, Williams, and Harkins observed that individuals working together put out less effort than when they work alone, an effect these researchers termed social loafing. Subsequent research (Williams, Harkins, & Latane, 1981) has suggested that this effect arises, at least in part, because when participants work with others on these tasks their individual outputs are lost in the crowd, and, thus, they can receive neither credit nor blame for their performances. However, it is unlikely that participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0
5

Year Published

1986
1986
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(85 citation statements)
references
References 16 publications
4
74
0
5
Order By: Relevance
“…Dieser Motivationsverlust wird auch als soziales Faulenzen (social loafing) bezeichnet (Karau und Williams 1993, 1995, 1997Latané, Williams, und Harkins 1979). (Brickner et al 1986;Harkins und Petty 1982). Diesen Befunden zufolge wird die Leistung im Falle subjektiv bedeutsamer Aufgaben nicht dadurch beeinflusst, ob diese in Gruppen oder alleine erbracht werden.…”
Section: Motivationsverlust Mit Negativen Auswirkungen: Soziales Faulunclassified
“…Dieser Motivationsverlust wird auch als soziales Faulenzen (social loafing) bezeichnet (Karau und Williams 1993, 1995, 1997Latané, Williams, und Harkins 1979). (Brickner et al 1986;Harkins und Petty 1982). Diesen Befunden zufolge wird die Leistung im Falle subjektiv bedeutsamer Aufgaben nicht dadurch beeinflusst, ob diese in Gruppen oder alleine erbracht werden.…”
Section: Motivationsverlust Mit Negativen Auswirkungen: Soziales Faulunclassified
“…Equity corresponds to the inverse of social loafing and correlates to the Collective Intelligence of a group, a factor that explains the group's performance on a wide variety of tasks (Woolley et al, 2010). Furthermore, our results showed that the attractiveness of the tabletop device increased extrinsic motivation to engage in the task, which is also a moderating factor of social loafing (Brickner et al, 1986;Shepperd, 1993).…”
Section: A Tabletop Interface For Brainwritingmentioning
confidence: 50%
“…A koordinációs veszteségek száma minimálisra csökken a vizsgálatok szerint, ha a feladat érdekes. Ilyenkor ez a külső motiváció is segít a csoportnak (Brickner, Harkins és Ostrom, 1986).…”
Section: A Kommunikációt Meghatározó Külső Tényezőunclassified